Penyuluhan Pengembangan Potensi Agribisnis Dan Pariwisata Di Desa Plumbon Kecamatan Tawangmangu Kabupaten Karanganyar - Setiyani, Rahmawati; Rahmawati, Esti Dwi; Rahmadhani, Istining (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Plumbon Village is one of the villages located in Tawangmangu District, Karanganyar Regency. Plumbon Village has a very strategic location and has the support for the development of the potential of the agribusiness and tourism sectors. The partner in this community service activity is Plumbon Village. The methods used in this community service are (1) identification of partner problems, (2) counseling on the development of agribusiness and tourism potential, (3) evaluation of activities. The problem faced by partners is that the potential in Plumbon Village has not been optimally utilized to improve community welfare. The purpose of this community service activity is to develop the potential of the agribusiness and tourism sectors in Plumbon Village. The development of the potential of the agribusiness and tourism sectors can be carried out with several strategies, including making tourism icons that have certain attraction such as educational tourism, utilizing social media account as a means of promotion, and making educational tourism posters. Based on the results of the implementation of community service, participants were enthusiastic in participating in the activity. It is hoped that this community service activity can provide new insights for partners and can have a positive impact on the progress of Plumbon Village and improve community welfare.